Gender differences in amplitude spectral area (AMSA) of ventricular fibrillation in patients with out-of-hospital cardiac arrest. (3rd October 2022) - Quilico, F; Vicini Scajola, L; Gentile, F R; Compagnoni, S; Baldi, E; Aramendi, E; Isasi, I; Lopiano, C; Primi, R; Bendotti, S; Currao, A; Contri, E; et al.
Abstract: Introduction: Ventricular fibrillation (VF) Amplitude Spectral Area (AMSA) is a well-established predictor of successful defibrillation and return of spontaneous circulation (ROSC). Attending to the limited evidence on the topic, gender seems to affect AMSA, and higher values have been reported in females. The aim of this work was to investigate the effect of gender in AMSA values for patients suffering out-of-hospital cardiac arrest (OHCA). Methods: We enrolled 4619 consecutive OHCA patients from January 2015 to December 2020 in the LombardiaCare Registry. We considered only those subjects with attempted cardio-pulmonary resuscitation (697 patients) and at least one shock delivered. A total of 250 patients were considered (40 F/ 210 M) with 830 shocks (100 F/ 730 M). AMSA values were computed for the ventricular fibrillation in the 2-s pre-shock interval of the ECG recorded by the Corpuls3 defibrillator (Corpuls, Kaufering, Germany). Results: Female patients were older than male [median (IQR): 70.5 (62–72) vs 67 (55–75) years, p=0.01], with cardiac arrest more frequently at home (84% vs 76%, p=0.003), fewer shocks [2 (1–4) vs 4 (2–7), p=0.004] and higher percentage of success (53% vs 40%, p=0.009). On the contrary, cardiac arrest duration [ 58.7 (31–69) vs 57.6 (41.4–77.3) min, p=0.366] and the rate of ROSC (32% vs 33%, p=0.88) were similar in both groups. Higher AMSA values were found in female patients [10.3 Hz-mV (6.6–13.5) vs 7.9 Hz-mV (5.2–12.1), p=0.0007]. At a multivariable analysis, after correction for witnessed status, bystanders CPR, amiodarone administration, age and call-to shock time, male sex was found to be independently associated with the probability of having low values of AMSA, below the median value of 8.3 Hz-mV [OR 2.15 (95% CI1.35–3.43), p=0.001]. Despite gender stratification ROC curve analysis confirmed AMSA as a predictor of shock success [AUC-F: 0.75 (95% CI 0.65–0.83), p<0.001; AUC-M: 0.78 (95% CI 0.74–0.81)] and ROSC [AUC-F: 0.69 (95% CI 0.59–0.68), p=0.008; AUCM: 0.84 (95% CI 0.81–0.87)]. Conclusion: Female sex is related to higher AMSA values. As AMSA reflects the energetical status and the ATP levels in the myocardial cells during cardiac arrest, this difference may be due to lower incidence and lower severity of cardiac ischemic disease in women. AMSA remains a valid predictor of both shock success and ROSC for female and male patients. Further investigations are needed to support and comprehend these conclusions. Funding Acknowledgement: Type of funding sources: None.